2019
DOI: 10.1021/acs.cgd.9b00999
|View full text |Cite
|
Sign up to set email alerts
|

Two Hg(II)-Based Macrocycles Offering Hydrogen Bonding Cavities: Influence of Cavity Structure on Heterogeneous Catalysis

Abstract: We present the synthesis and characterization of two Hg-macrocycles offering H-bonding based cavities of varying dimensions. Both Hg-macrocycles illustrate a noteworthy difference in their catalytic performance that has been related to their cavity structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 75 publications
2
46
0
Order By: Relevance
“…Both Ru­(II) ions in 1 exhibited a six-coordinate distorted octahedral geometry. The Ru–P, Ru–Cl, and Ru– p -cymene bond distances were comparable to the literature examples. ,, Importantly, two Ru­(II) ions are coordinated in such a way that the pyridine-2,6-dicarboxamide based pincer cavity of the ligand remained intact. , …”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Both Ru­(II) ions in 1 exhibited a six-coordinate distorted octahedral geometry. The Ru–P, Ru–Cl, and Ru– p -cymene bond distances were comparable to the literature examples. ,, Importantly, two Ru­(II) ions are coordinated in such a way that the pyridine-2,6-dicarboxamide based pincer cavity of the ligand remained intact. , …”
Section: Resultssupporting
confidence: 83%
“…Notably, the presence of the water molecule within the pincer cavity forces one of the RuCl 2 fragments facing inward. Importantly, existence of a H 2 O molecule H-bonded within the pincer cavity of 1 suggests the possibility of a suitable substrate being held in place closer to the Ru­(II) center(s) and such a situation may help in the catalysis (vide infra) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further evidence were obtained from the molecular docking studies for all three complexes to that of PA (Figure 7; Figures S37 and S38). 86 The docked structure of the picrate ion with complex 3 showed that the O phenol atom of the picrate ion coordinated with the Ni(II) ion with a bond distance of 2.353 Å. In addition, one of the protonated benzimidazolium rings created an H-bond with the O phenol atom of the picrate ion (N5−H1••• O picrate ) with a N•••O heteroatom separation of 3.829 Å.…”
Section: ■ Introductionmentioning
confidence: 99%